Kinetic analysis of ex vivo human blood infection by Leishmania. - Inmaculada Moreno; Mercedes Domínguez; Darío Cabañes; Carmen Aizpurua; Alfredo Toraño (Public Library of Science (PLoS), 2010)
The leishmanioses, vector-borne diseases caused by the trypanosomatid protozoan Leishmania, are transmitted to susceptible mammals by infected phlebotomine sand flies that inoculate promastigotes into hemorrhagic pools created in host skin. We assumed that promastigotes are delivered to a blood pool, and analyzed early promastigote interactions (0-5 min) with host components, which lead to parasite endocytosis by blood leukocytes, and to host infection. Promastigotes were incubated with NHS or with heparinized blood in near-physiological conditions, and we used cell radioimmunoassay and flow cytometry to measure the on-rate constants (k(+1)) of promastigote interactions with natural opsonins and erythrocytes. We obtained quantitative data for parasitized cells to determine the time-course of promastigote binding and internalization by blood leukocytes. In these reactions, promastigotes bind natural opsonins, immune adhere to erythrocytes and activate complement cytolysis, which kills approximately 95% of promastigotes by 2 min post-infection. C3-promastigote binding is a key step in opsonization; nascent C3-promastigotes are the substrate for two simultaneous reactions, C3-promastigote immune adherence (IA) to erythrocytes and complement-mediated promastigote killing. The k(+1) for IA was 75-fold greater than that for promastigote killing, showing that IA facilitates promastigote endocytosis and circumvents lysis. At 5 min post-infection, when reaction velocity is still linear and promastigote concentration is not limiting, 17.4% of granulocytes and 10.7% of monocytes had bound promastigotes, of which approximately 50% and approximately 25%, respectively, carried surface-bound (live) or internalized (live and dead) leishmanias. Of other leukocyte types, 8.5% of B cells bound but did not internalize promastigotes, and T cells, NK cells and CD209(+) dendritic cells did not bind parasites. These data show that, once in contact with blood, promastigote invasion of human leukocytes is an extremely rapid and efficient reaction, and suggest that the IA reaction constitutes a central strategy for this parasite in subverting host innate immune defenses.